Botany, Informal Empire and the Colonial Roots of British Gardens - Frances O’Morchoe (Revue Française de Civilisation Britannique)
This article investigates the practices of colonial science through a study of one plant collector working for the Chinese Maritime Customs Service, an institution of Britain’s informal empire in China. Further, the article situates this collector and his work in the context of the boom in popular gardening in Britain at the time. Popular garden writing in the late 19th and early 20th century helped fold China’s temperate plants into the canon of “natural” British plants. I argue that garden writers used a “temperate imagination” to encourage readers to imagine the connections between their own gardens and the temperate realms of Britain’s empire. These authors, and the plants they described, helped bring empire home to amateur gardeners in Britain.